Hubungan Pengetahuan Ibu, Tingkat Pendidikan, Pendapatan, Pola Asuh Makan, dengan Status Gizi Balita di Wilayah Kerja Puskesmas Mata Kendari Sulawesi Tenggara - Gani, Kameriah; Misriani, Misriani (Jurnal Gizi Ilmiah, 2016)
Malnutrition and malnutrition are health problems that are commonly found in developing countries. Nationally, the prevalence of underweight in 2013 was 19.6%, consisting of 5.7% of malnutrition and 13.9% of undernourished. The purpose of the study was to determine the relationship between mother's knowledge, education level, income, eating patterns, and the nutritional status of children under five in the eye health center working area. This research was an analytical descriptive study with a cross sectional approach. This research was conducted on 10 October – 27 December 2016 in the Eye Health Center Working Area with a total of 90 samples. The sampling technique used is purposive sampling, which is not random, but the researcher determines the sample to be taken. independent variables include mother's knowledge, mother's education, level of family income, eating patterns, and nutritional status as the dependent variable. Mother's knowledge percentage is mostly 51.1% in good category, Mother's education is mostly 54.4% in Low education category, Family income is mostly 69.2% in adequate category, Parenting pattern is mostly 62.2% in normal category, Nutritional status is mostly large 72.2% normal category. There is a relationship between mother's knowledge and nutritional status of toddlers, There is no relationship between education level and nutritional status of toddlers, There is no relationship between income and nutritional status of toddlers, There is a significant relationship between eating parenting patterns and nutritional status of toddlers. There is a significant relationship between mother's knowledge, and parenting eating patterns with the nutritional status of toddlers, there is no relationship between maternal education, family income, and nutritional status of children under five.